Long non-coding RNA slincRAD functions in methylation regulation during the early stage of mouse adipogenesis. Issue 10 (3rd October 2019) - Yi, Fan; Zhang, Pei; Wang, Yao; Xu, Yin; Zhang, Zhengxi; Ma, Weizhi; Xu, Bo; Xia, Qing; Du, Quan
ABSTRACT: Adipocyte differentiation is a coordinated cellular process, which involves a series of dynamic molecular events. Up-regulation of long noncoding RNA slincRAD expression was found to occur in the early differentiation stages of 3T3-L1 cell, prior to the regulation of major transcription factors. By interacting with DNMT1 in S phase, slincRAD guides this essentially epigenetic factor to mediate promoter methylation of a batch of cell cycle-related genes, including cyclin-dependent kinase inhibitor p21 . The regulation promotes the growth-arrested cells to re-enter into cell cycle under hormone induction and thereby advances the process of differentiation to clonal expansion stage. The abolishment of the interaction between slincRAD and DNMT1 by slincRAD knockdown results in a defective epigenetic regulation and finally compromised adipogenesis. Collectively, our study characterizes the epigenetic regulation of lncRNA involved in the early stage of adipogenesis.